Many minds make money: People are slower to destroy novel currency known to more ingroup members. (31st March 2021) - Shteynberg, Garriy; Kwon, Theresa A.; Yoo, Seong‐Jae; Smith, Heather; Apostle, Jessica; Mistry, Dipal; Houser, Kristin
Abstract: If asked to destroy a dollar bill, one would likely hesitate. After all, the destruction of the dollar bill equals the loss of its economic value. Yet the reluctance to destroy a dollar bill may also stem from social knowledge—the fact that it exists in the minds of many members of one's valued group. Here, we investigate whether social knowledge of money increases people's reluctance to destroy it. We create a fictional currency and vary the social knowledge of its existence across experimental conditions. Results across three studies suggest that people are slower to destroy more socially known currency without liking it more. Our findings suggest that money can be respected when it is merely known by many, without being necessarily liked by them.